Effect of iron deficiency without anaemia on days alive and out of hospital in patients undergoing valvular heart surgery. (9th March 2022) - Kim, H. B.; Shim, J. K.; Ko, S. H.; Kim, H. R.; Lee, C. H.; Kwak, Y. L.
Summary: Comprehensive evidence regarding the treatment of non‐anaemic iron deficiency in patients undergoing valvular heart surgery is lacking. This study aimed to investigate the association between non‐anaemic iron deficiency and postoperative outcomes in these patients. We retrospectively analysed 321 patients of which 180 (56%) had iron deficiency (defined as serum ferritin < 100 ng.ml ‐1 or < 300 ng.ml ‐1 with transferrin saturation < 20%). While the iron‐deficient group had lower pre‐operative haemoglobin levels than the non‐iron deficient group (median (IQR [range]) 134 (127–141 [120–172]) g.l ‐1, 143 (133–150 [120–179]) g.l ‐1, p = 0.001), there was no between‐group difference in allogeneic red blood cell transfusion. Median (IQR [range]) days alive and out of hospital at postoperative day 90 was 1 day shorter in the iron‐deficient group (80 (77–82 [9–85]) days vs. 81 (79–83 [0–85]) days, p = 0.026). In multivariable analysis, only cardiopulmonary bypass duration (p = 0.032) and intra‐operative allogeneic red blood cell transfusion (p = 0.011) were significantly associated with reduced days alive and out of hospital at postoperative day 90. Iron deficiency did not exert any adverse influence on secondary outcomes except length of hospital stay. Our findings indicate that non‐anaemic iron deficiency alone is not associated with adverse effects in patients undergoing valvular heart surgery when it does not translate into an increased risk of allogeneic transfusion.